Comparison of 3D aerodynamic models for vertical-axis wind turbines: H-rotor and Φ-rotor. Issue 5 (September 2020) - Tavernier, D. De; Sakib, M.; Griffith, T.; Pirrung, G.; Paulsen, U.; Madsen, H.; Keijer, W.; Ferreira, C.
Abstract: Since the first commercial projects, the development of vertical-axis wind turbines (VAWTs) has been impeded by the limited understanding and inability to accurately model VAWTs. This paper investigates and compares different aerodynamic modelling techniques for VAWTs in 3D. All considered models are using the same blade-element characteristics but use different descriptions to determine the induced velocity field. The H-and Φ-rotor are studied with various aspect ratios and rotor loadings. Both instantaneous azimuthal parameters as well as integral parameters, such as the thrust and power are investigated. The paper concludes that capturing the 3D effects of VAWTs is challenging and the trends to be expected are not straightforward due to the complex vortex system created by VAWTs. All model assumptions affect the results both at the mid-plane of the rotor as well as at the blade tips.